The early outcomes of two separate anastomosis procedures in deceased kidney transplantation with double arteries: A retrospective comparative study - Changyu Ma; Congrong Shen; Hao Dong; Chonghao Sun; Jianfeng Wang; Zhenshan Ding; Xing Chen; Yangtian Jiao; Xiaohong Ren; Xiaofeng Zhou (Asian Journal of Surgery)
Background: Kidneys with double renal arteries are used on a routine basis nowadays, and separate anastomosis in situ is one of the suitable arterial anastomosis procedures. The commonly used methods are parallel end-to-side anastomoses of double arteries to the external iliac artery, and end-to-end anastomosis to the internal iliac artery combined with end-to-side anastomosis to the external iliac artery. No studies have compared the prognoses of the two procedures in deceased kidney transplantation. Methods: We retrospectively analyzed 35 consecutive deceased kidney transplantations with double arterial anastomoses in the urology department of China–Japan Friendship Hospital from January 2018 to April 2021. Group I comprised recipients with double parallel end-to-side anastomoses to the external iliac artery; Group II comprised the others. Their prognoses were then compared. Results: There were no significant differences between Group I and II in characteristics of recipients and donors. The mean eGFRs at 1, 3, 6 and 12 months post-transplant in Group I and II were 36.4 vs 54.1 (P = 0.009), 40.4 vs 54.4 (P = 0.02), 40.4 vs 56.9 (P = 0.02) and 39.8 vs 57.9 (P = 0.007) mL/min respectively. There was no difference in early postoperative complications and 1-year survival rates between the two groups (P = 1.00). Conclusion: Separate anastomosis is a reliable procedure for deceased kidney transplantation with double arteries. Double separate anastomoses to the external and internal iliac arteries have better graft function compared with double parallel anastomoses to the external iliac artery during the first year after transplantation.